Implementasi Tazkiyatun Nafs Melalui Dzikir dan Shalawat Perspektif Imam Al-Ghazali Studi di Pondok Pesantren Sirajut Thalibin - Rofi Sanjoko; Ahmad Muzakki; Hawa’ Hidayatul Hikmiyah (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to analyze the implementation of tazkiyatun nafs through dhikr and shalawat from the perspective of Imam Al-Ghazali at the Sirajut Thalibin Islamic Boarding School. The background of this study is based on the importance of spiritual development in Islamic education as an effort to face the moral crisis and moral degradation of the young generation in the modern era. The concept of tazkiyatun nafs is seen as a process of purifying the soul that can form inner peace, self-control, and noble morals through the habituation of spiritual worship such as dhikr and shalawat. This study uses a qualitative approach with a case study research type. Data collection techniques are carried out through observation, interviews, and documentation of the boarding school leaders, ustaz, and students. The results of the study indicate that the implementation of tazkiyatun nafs at the Sirajut Thalibin Islamic Boarding School is carried out through routine dhikr activities, congregational recitation of shalawat, adab development, and teacher role models in daily life. This practice has a positive impact on the formation of the religious character of students, such as increased discipline, peace of mind, humility, and spiritual closeness to Allah SWT. Imam Al-Ghazali's perspective on the purification of the soul through spiritual self-expression has proven relevant in the formation of the spirituality of students in modern Islamic boarding schools. This research contributes to the development of Sufism-based Islamic education as an approach to developing the character and spirituality of students.